Getting out : early release in England and Wales, 1960-1995 - Guiney, Thomas (Oxford : Oxford University Press, 2018)
'Getting Out' explores the evolution of early release in England and Wales between 1960-1995. In recent years crime has become a highly contested political issue with implications for the humanity, fairness and effectiveness of the criminal justice system. This book turns current crime debate on its head and examines the circumstances in which politicians and policy-makers have found it desirable to reduce the custodial element of a prison sentence and encourage the rehabilitation of offenders in the community. Drawing upon a period of detailed archival research this book considers three critical moments of reform which have helped to shape the historical evolution of this secretive and little understood area of public policy.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 30, 2018).
Keywords: Early release programs -- England -- History -- 20th century; Early release programs -- Wales -- History -- 20th century; True Crime; Social services & welfare, criminology